Ideas and Thoughts on Islamic Education from Fazlur Rahman's Perspective - Bambang Sutikno (Maklumat: Journal of Da'wah and Islamic Studies, 2023)
Education is an integral part of human life. Even in the present time, education has become an immensely vital necessity. Fazlur Rahman, a modern Muslim scholar, endeavored to connect Islamic education with the modern context. Despite being renowned as an expert on the Quran, he also paid attention to other aspects such as Islamic education. This commitment is reflected in various books he authored, including works that delve into educational topics. The research method employed in this piece is literature review. This paper discusses Islamic education. Based on Fazlur Rahman's perspective on education, two models originate from his ideas. First, a critical and creative Islamic education. Second, an Islamic education that upholds high moral standards.